Finite element simulation of wire's sag considering tension insulator string. (May 2022) - Zhang, Ruiyong; Zhao, Xinyu; Shen, Guohui; Yao, Jianfeng
Abstract: A finite element simulation process based on methods of mutual calling between MATLAB and ANSYS software packages are proposed, which has the ability to consider the influence of tension insulator string weight on the sag of a span in a tension section. The convergence criterion of the process can be controlled artificially and is defines to converge when the maximum sag of two calculation steps is very small. A simplified theoretical analysis method is also developed for comparison and verification. These proposed methods are then applied to a tension section and a three-span actual line. Results show that when using a finite element simulation to obtain the curve of a wire, if the number of elements in the span is 10, the mid-span sag in the span is consistent with the theoretical result. And if the number of elements in the span is greater than 50, the sag curve of the conductor is almost unchanged. The two methods and the difference between them are very small, indicating the efficiency of the proposed process.